Automatic on-Demand Selection of Suitable Wireless Scheduling Algorithm to Minimize Queue Overflow Probability - Vineeth, S; Vadivel, R (International Journal of Computer Sciences and Engineering, 2020)
In this paper, it is been studied the robustness of light traffic obtained by the tuning algorithm for various traffic networks. Since processing the programming algorithm is unaffected using the standard mathematical tool, the aim is to reduce the maximum likelihood of saturation obtained by the algorithm. In large deviation settings, this problem is equivalent to increasing the amount of asymptotic decomposition of the maximum possible. It is start by getting more of the decaying level of the fullness of the line as the line's fullness decays closer to infinity. Subsequently, made study several structural properties of the low-cost method of linear saturation in a large length, which is an approximation to the decay rate of the largest saturation point. Given these properties, proven that the line with the largest length follows the sample path that extends through the line. At a certain parameter value, the sorting algorithm is very good at reducing the length of the largest line. For numerical results, it is have shown the large-scale deviation properties of the line lengths that are commonly used while varying one algorithm parameter.